Understanding Human Movement Patterns within Cislunar Habitats - Litaker, Harry; Bekdash, Omar; Chappell, Steve; Beaton, Kara; Gernhardt, Michael (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2020)
In preparation for testing five Broad Agency Announcement (BAA) commercial cislunar habitat designs, the National Aeronautics and Space Administration (NASA) embarked on a yearlong in-house training program. This consisted of in-house testing for subject matter experts (SMEs) and crew to informed and ensure evaluation data collection techniques for each of the contractor options. Many evaluation techniques were tested with some continuing forward. Two-test conditions were employed - 1) habitat centric functions with one space element and 2) distributed functions across two or more space elements. This paper will look at one of these techniques—human circulation patterns—to assess a spacecraft habitat’s internal configuration while the crew is working a three day simulated cislunar mission. Real time tracking of the crew was accomplished using the AllTraq© system of ultra- wideband frequency (UWB) receivers and radio frequency identification tags (RFID). Heat maps, Zone Time Histograms, Zone Time Utilizations Tables and Task/Time Density Tables were constructed from the collected data. Results indicated distributing functions across elements decreased crew interference and task wait times. Additionally, areas of underutilization were located, which lead to interior layout design changes.